International Capital Markets : Developments, Prospects, and Key Policy Issues 1997. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
Provides a comprehensive survey of recent developments in international financial markets, including developments in emerging capital markets, bond markets, major currency markets, and derivative markets. The report focuses on efforts by the major industrial countries to strengthen the management of financial risk and prundential oversight over the international banking system. It also critically evaluates existing mechanisms for international cooperation of financial supervision and regulation and proposes the development of international banking standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet